The Relationship Between Mother’s Knowledge and Diversity of Complementary Feeding Aged 6-23 Month in Karang Mekar Village Banjarmasin City - Noraini; Putri Fauziah Bilqis; Yanti, Rusmini (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2025)
The practice of giving MP-ASI is an important factor for children's nutritional needs because starting at the age of 6 months there is a nutritional inequality between the amount needed and the energy and nutritional substances available from breast milk that it must from MP-ASI. World Health Organization (WHO) in 2018 stated 32% of toddlers in developing countries suffer from stunting and 10% wasting is caused MP-ASI which is not optimal. In theory knowledge will determine person's behavior including a mother. In maintaining the health of the baby, especially in the provision of proper complementary feeding, mother is required to have high knowledge so that complementary feeding is varied and has appropriate nutrients. This research aims to find out the Relationship of Mother's Knowledge with the Diversity of Feeding 6-23 Months in Karang Mekar. The method in this study is a quantitative method using a cross sectional design. The population is all toddlers aged 6-23 months in Karang Mekar Village. The collection of maternal knowledge data and the diversity of MP-ASI by interviewing using a questionnaire. Data analysis using spearman test rank. The results showed that toddlers in the study were 8.7% 6-8 months, 15.2% 9-11 months, and 76.1% 12-23 months with 1:1 male and female gender ratio. Characteristics of toddler mothers based on knowledge 43.5% good, 39.1% moderate, and 17.4% less. Toddlers get MPASI vary 69.6% and not vary 30.4%. Research shows that there is a relationship between mother's knowledge and the diversity of MP-ASI in toddlers 6-23 months